Knowing the Basics About 4-H Clubs - Marilyn N. Norman; Joy C. Jordan (EDIS, 2006)
The 4-H club serves as the primary means of providing youth development programming in 4-H. It has the advantage of long-term involvement with the support of caring adults. This document is 4-HS FS101.6, one of a series of the Florida 4-H Program, UF/IFAS Extension. Published May 2006.